2003
DOI: 10.1109/tvcg.2003.1175094
|View full text |Cite
|
Sign up to set email alerts
|

Improving the robustness and accuracy of the marching cubes algorithm for isosurfacing

Abstract: This paper proposes a modification of the Marching Cubes algorithm for isosurfacing, with the intent of improving the representation of the surface in the interior of each grid cell. Our objective is to create a representation which correctly models the topology of the trilinear interpolant within the cell and which is robust under perturbations of the data and threshold value. To achieve this, we identify a small number of key points in the cell interior that are critical to the surface definition. This allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 14 publications
(23 reference statements)
0
94
0
1
Order By: Relevance
“…In order to overcome such shortcomings of MC, several extensions are discussed in the literature [3], [4], [5], [16], [21], [23], [24], [33], [34], [35]. To obtain a high-quality triangle mesh from MC, postprocessing steps are typically applied directly to the triangle mesh [10].…”
Section: Related Workmentioning
confidence: 99%
“…In order to overcome such shortcomings of MC, several extensions are discussed in the literature [3], [4], [5], [16], [21], [23], [24], [33], [34], [35]. To obtain a high-quality triangle mesh from MC, postprocessing steps are typically applied directly to the triangle mesh [10].…”
Section: Related Workmentioning
confidence: 99%
“…The function values of face and body saddles in the cell can be used to decide the correct topology and consistent triangulation of an isosurface in the cell [42]. Lopes and Brodlie [38] provided a more accurate triangulation.…”
Section: Previous Work Isosurface Extractionmentioning
confidence: 99%
“…Several cases may have more than one local topology, and are termed ambiguous. We refer to [38] for all the cases of different local topology of an isosurface in a cube. When a case is ambiguous, the standard dual contouring method causes a non-manifold at the minimizing vertex in the cube.…”
Section: Mesh Topologymentioning
confidence: 99%
“…As algorithms and implementations become more complex, issues may be overlooked and remain hidden in the multitude of (pseudo-) lines of code. Throughout years of research, it has been shown that some supposedly topologically correct techniques, including MC33, have issues that prevent correctness [7,16,21]. In particular, the work of Etiene et al [7] shows that the MC33 implementation by Lewiner et al [14,15], fails to produce topologically correct isosurfaces.…”
Section: Introductionmentioning
confidence: 99%